Foreign deficit and economic policy - Huerta González, Arturo (Levy Economics Institute, 2024)
The article analyzes Mexico under globalization, particularly on the free mobility of capital. It argues that globalization has detrimentally impacted the productive and external sectors, causing the economy to become excessively reliant on volatile capital inflows from abroad. The Mexican government-instead of undoing the structural problems that lead to external deficits- implements policies that resolve the short-term liquidity needs and go against economic growth, as if they are promoting capital inflows. The national currency has appreciated greatly and acts only in favor of the financial sector and in detriment of the productive and the external sector. The Mexican economy has fallen into a context of high external vulnerability since it rests on capital inflows. Capital inflows are highly fragile and volatile. They depend not only on internal problems, but also on the world economy and expectations. For this reason, the reliance on capital inflows to appreciate the peso is unsustainable. Given the meager growth of the world economy and trade, globalization is being questioned and various countries are implementing industrial and protectionist policies. If Mexico continues to bet on outward growth through nearshoring, it will have no chance of overcoming the problems it faces. Mexico cannot continue with an economic policy that does not generate endogenous conditions to growth and that has made the economy dependent on the behavior of international financial markets which generate recurrent crises.
10419/300503
Keywords: Graue Literatur; Capital Inflow; Capital Mobility; Exchange Rate; Foreign Investment; Free Trade; Interest Rates; International Capital Movement; Monetary Policy; Stabilization; Trade Liberalization